Clouding or Clarifying? Using the Bible to Explore the Scottish Independence Referendum Question. Issue 3 (2nd October 2015) - Stoddart, Eric
Abstract : This article reports on one dimension of a series of focus groups conducted mostly in the summer of 2014, in which participants were facilitated through a cycle of practical theological reflection to consider their impending decision in the referendum on Scottish independence. Attention here is given to the range of biblical passages which the participants themselves brought to the discussion. These are categorised under three headings: an issue, the manner of the debate, and political theory. A detailed account and analysis are offered of a text around social justice and another adopting a virtue ethics standpoint. Boff's "correspondence of relationships" hermeneutic sheds light on the sophisticated approach that participants took to the use of the Bible to consider a pressing political question on which a dichotomous answer was required in the ballot box.